Analysis of the Influence of Fintech on the Development of Clothing MSMEs in the Medan Petisah Market - Haikal, Muhammad; Munthe, Yeyen Aprilia; S, Khawarizmi Annadi; Siregar, Zulkarnain; Khaira, Imamul (Economic: Journal Economic and Business, 2024)
The research will focus on the impact of Fintech in developing clothing SMEs at Petisah Market. The primary data used in this research will come from observations and interviews conducted directly in the field with participating informants. This study aims to analyze the impact of Fintech on payment processes, sales channel diversification, access to financing, and financial management in the context of clothing SMEs at Petisah Market. By gaining a deeper understanding of the impact of Fintech, it is expected that SMEs can utilize it optimally to grow and advance their businesses. Through this research, stakeholders, such as clothing SMEs at Petisah Market, the government, and financial institutions, are expected to gain useful insights into the potential and benefits of Fintech and the extent to which it can contribute to addressing challenges and promoting the development of SMEs in the clothing industry